Intraosseous Capillary Hemangioma of the Nasal Dorsum in an Adolescent - Soehartono Soehartono; Rizky Afianti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Hemangioma is a benign vascular tumor that commonly occurs in children, but its presentation on the nasal dorsum is rare, especially among adolescents. This case report describes a 16-year-old male patient with a progressively enlarging, painful nasal mass over seven months. Clinical workup including CT-scan, angiography, and FNAB revealed a vascular lesion suggestive of hemangioma. The patient underwent pre-operative embolization followed by surgical excision. Histopathological and immunohistochemical evaluations confirmed the diagnosis of intraosseous capillary hemangioma. Postoperative follow-up showed good aesthetic and functional outcomes with no recurrence. This report highlights the importance of comprehensive diagnostic and surgical approaches for managing rare hemangioma of the nasal dorsum to minimize complications and preserve facial structure.